Transcriptome and Metabolome Analyses Reveal Molecular Responses of Two Pepper (Capsicum annuum L.) Cultivars to Cold Stress - Zhang, Jianwei; Liang, Le; Xie, Yongdong; Zhao, Zhao; Su, Lihong; Tang, Yi; Sun, Bo; Lai, Yunsong; Li, Huanxiu (Frontiers in Plant Science, 2022)
Low temperature is a significant factor affecting field-grown pepper. The molecular mechanisms behind peppers’ response to cold stress remain unknown. Transcriptomic and metabolomic analyses were used to investigate the responses of two pepper cultivars, XS (cold-sensitive) and GZ (cold-resistant), to cold stress; these were screened from 45 pepper materials. In this study, compared with the control group (0 h), we identified 10931 differentially expressed genes (DEGs) in XS and GZ, 657 differentially expressed metabolites (DEMs) in the positive ion mode, and 390 DEMs in the negative ion mode. Most DEGs were involved in amino acid biosynthesis, plant hormone signal transduction, and the mitogen-activated protein kinase (MAPK) signaling pathway. Furthermore, metabolomic analysis revealed that the content of free polyamines (PAs), plant hormones, and osmolytes, mainly contained increased putrescine, spermine, spermidine, abscisic acid (ABA), jasmonic acid (JA), raffinose, and proline, in response to cold stress. Importantly, the regulation of the ICE-CBF-COR pathway by Ca2+ signaling, MAPK signaling, and reactive oxygen species (ROS) signaling plays a key role in regulating responses of peppers to cold stress. Above all, the results of the present study provide important insights into the response of peppers to cold stress, which will reveal the potential molecular mechanisms and contribute to pepper screening and breeding in the future.